FEATURES TRANSFORMATION OF THE RUSSIAN STATE IDENTITY POLICY IN THE CONTEXT OF NEW GEOPOLITICAL CHALLENGES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The article researches the transformation of the Russian state identity policy in response to new geopolitical challenges. The features of the formation and modification of the official normative representation of national identity in Russia at the present stage are conceptualized. Russian identity policy has undergone significant changes in recent years due to new geopolitical challenges. This research examines how the national identity of the country developed in response to changes in the system of international relations. The scientific novelty of this article consists in the proposed research optics focused on the intersection of identity politics and geopolitics in the Russian context. The presented research analyzes the concept and content of the state identity policy of the Russian Federation, its transformation in recent years, and also structures the mechanisms and tools of state policy in the field of identity formation. The empirical basis of the research is the conceptual normative legal documents defining the key directions of the implementation of the identity policy of the Russian Federation, which have undergone changes during the period under review, as well as policy statements by representatives of the federal political elite on this issue in the same time interval. The purpose of the study is to identify key changes in the officially declared directions of state identity policy in the context of ongoing global geopolitical processes. In conclusion, the article presents the results of the analysis of the transformation of the policy of the Russian state identity in the context of new geopolitical challenges.